1989
DOI: 10.1016/0147-619x(89)90041-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromones and plasmid transfer in Enterococcus faecalis

Abstract: Plasmid-free Enterococcus faecalis excrete peptides (sex pheromones) which specifically induce a mating response in strains harboring certain conjugative plasmids. The response is characterized by the synthesis of a "fuzzy" surface material, visible by electron microscopy, which is believed to facilitate the aggregation of donors and recipients. Transconjugants which receive a specific plasmid shut down the production of endogenous pheromone; however, they continue to produce pheromones specific for donors har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
85
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 37 publications
2
85
0
Order By: Relevance
“…(pAM2030 contains the A3 deletion [see Fig. 1] and was previously shown to allow cADi production [2,13]). As shown in the table, two of the double-insert plasmids, pAM2045 and to a lesser extent pAM2145, allowed production of cADl in an OGlX background.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(pAM2030 contains the A3 deletion [see Fig. 1] and was previously shown to allow cADi production [2,13]). As shown in the table, two of the double-insert plasmids, pAM2045 and to a lesser extent pAM2145, allowed production of cADl in an OGlX background.…”
Section: Resultsmentioning
confidence: 99%
“…These results were somewhat surprising, since no single E or C region insert or traB single insert which results in cAD1 production has been isolated. The A3 deletion present on pAM2030 disrupts both the C region and traB (2), providing yet another mutant combination resulting in failure to shut down cAD1. The two combinations involving traB (pAM2030 and pAM2045) were least effective in pheromone shutdown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of pure cultures of donor cells to culture filtrates of recipients (12) or to purified peptide pheromones (30,31,33) can induce self-clumping of the donor cells, with kinetics resembling those of the induction of high-frequency transfer ability (30). These observations have been incorporated into a model (6,10,13) which postulates that the pheromone response of donor cells includes the synthesis of a plasmiddetermined surface adhesin, aggregation substance (AS), which mediates attachment to recipient cells via a chromosomally encoded receptor, binding substance (BS). Because donor cells also express BS, they will aggregate with other donor cells, but the subsequent plasmid transfer between aggregated donors appears to be inhibited by a pheromoneinducible surface exclusion mechanism (16).…”
mentioning
confidence: 99%
“…Most of this work has focused on three pheromone-inducible plasmids, including the hemolysinbacteriocin plasmid pAD1 (17), the bacteriocin plasmid pPD1 (41), and the tetracycline resistance plasmid pCF10 (14). In the case of the former two plasmids, immunoblotting analysis of cell surface extracts prepared with the detergent Zwittergent (6,20) led to the suggestion that a 78-kDa protein antigen was involved in aggregation. Similar analysis of the pCF10 system, which utilized primarily lysozyme extracts, suggested that a 150-kDa protein (formerly Tral50), now called AsclO, was involved in mating aggregate formation (4,30).…”
mentioning
confidence: 99%